Green tea extract modulates oxidative tissue injury in beta-thalassemic mice by chelation of redox iron and inhibition of lipid peroxidation - Pimpisid Koonyosying (2018)
© 2018 Elsevier Masson SAS Iron overload in patients with β-thalassemia can cause oxidative organ dysfunction. Iron chelation along with antioxidant supplementation can ameliorate such complications and prolong lives. Green tea extract (GTE) rich in epigallocatechin-3-gallate (EGCG) exhibits anti-oxidation and iron chelation properties in β-knockout thalassemic (BKO) mice diagnosed with iron overload. We investigated the effects of GTE and deferiprone (DFP) alone in combination with one another, and upon the levels of redox-active iron, lipid-peroxidation product, insulin and hepcidin in BKO mice. A state of iron overload was induced in the mice via a trimethylhexanoyl-ferrocene supplemented (Fe) diet for 3 months, and the mice were treated daily with either: DFP (50 mg/kg), DFP (50 mg/kg) plus GTE (50 mg EGCG equivalent/kg), or GTE alone for 2 months. Plasma non-transferrin bound iron (NTBI), malondialdehyde (MDA), alanine aminotransferase (ALT), aspartate aminotransferase (AST), hepcidin and insulin; tissue iron and MDA were measured. DFP, GTE and GTE + DFP effectively decreased plasma MDA (p < 0.05), NTBI and ALT, and increased plasma hepcidin and insulin. All the treatments also reduced iron accumulation and MDA production in both the pancreas and liver in the mice. However, the combination therapy demonstrated no advantages over monotherapy. The findings suggest GTE improved liver and pancreatic β-cell functions in iron-overloaded β-thalassemia mice by diminishing redox iron and free radicals, while inhibiting lipid peroxidation. Consequently, there are indications that GTE holds significant potential for clinical use.